Molecular detection of Anaplasma phagocytophilum in hair and spleen of cats revealed a possible underestimation of feline vector-borne pathogens. (July 2021) - Balboni, Andrea; Urbani, Lorenza; Morini, Maria; Dondi, Francesco; Battilani, Mara
Abstract: Feline Vector-Borne Diseases show increased global prevalence and some Anaplasma and Ehrlichia species may pose a risk to human health. The diagnosis of Anaplasma and Ehrlichia species infection in cats is achieved by the combined use of different methods as cytologic examination evidencing intracytoplasmic morulae, serologic tests and molecular assays. The peripheral whole blood is considered the sample of choice for Anaplasma and Ehrlichia species DNA detection in cats, but false negative results are reported leading to underestimation of infection prevalence. In order to have a more accurate assessment of the spread of feline vector-borne pathogens, the presence of Anaplasma spp. and Ehrlichia spp. DNA in 37 owner and shelter cats subjected to necropsy were prospectively investigated by testing in end-point PCR spleen, bone marrow, blood clot and hair samples. The bacteria identified were genetically characterised. Three shelter cats tested positive for A. phagocytophilum DNA in spleen (one cat) or in hair samples (two cats). None of the cats tested positive in bone marrow and blood samples. From the results obtained, it can be assumed that the use of spleen or hair samples could allow a more reliable detection of A. phagocytophilum DNA in cats with blood tested negative. In the phylogeny constructed with a fragment of the heat shock (groEL) gene nucleotide sequences, all the identified A. phagocytophilum clustered with bacteria infecting a wide range of hosts, including humans, showing a potential zoonotic role. Highlights: Owner and shelter cats were tested for the presence of Anaplasma and Ehrlichia DNA Spleen and hair samples allow reliable detection of A. phagocytophilum DNA in cats The A. phagocytophilum identified are potentially zoonotic